2017
DOI: 10.4274/tjh.2016.0434
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Interleukin-6, Interleukin-8 and Interleukin-10 for predicting bacteremia in children with febrile neutropenia

Abstract: Despite improvements in diagnosis and treatment, infections are still a major cause of morbidity and mortality in children with febrile neutropenia. In the majority of febrile episodes, the source of infection cannot be defined. In this study, we aimed to identify the earlier predictors of bacteremia/fungemia and a useful cytokine to identify the source of infection and to discriminate the patients with culture-confirmed bacterial/fungal infection. The most sensitive cytokine was interleukin (IL)-10 and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…At a cut-off value of 170 pg/ml, IL-8 correlated with all cases of gram-positive bacteraemia and 6/7 of gram-negative bacteraemia. Our result is consistent with recent evidence correlating IL-8 with bacteraemia in paediatric haematological patients, especially in Gram-negative bacteraemia 1821…”
Section: Discussionsupporting
confidence: 93%
“…At a cut-off value of 170 pg/ml, IL-8 correlated with all cases of gram-positive bacteraemia and 6/7 of gram-negative bacteraemia. Our result is consistent with recent evidence correlating IL-8 with bacteraemia in paediatric haematological patients, especially in Gram-negative bacteraemia 1821…”
Section: Discussionsupporting
confidence: 93%
“…Sixteen of these (41.6%) found significant associations between elevated CRP and bacterial infection, either microbiologically or clinically confirmed. Moreover, 14/16 significant studies provided predictive data with various cutoff values (range: 5–120 mg/L) ( 6 , 9 , 31 , 33 , 35 , 37 , 39 , 40 , 48 , 53 , 55 , 62 , 63 , 74 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies report the predictive data. Sahbudak et al ( 62 ) reported a sensitivity of 92.9% and specificity of 44.4% for a cutoff of 5.04 pg/ml in predicting a bacterial infection.…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin-10, an anti-inflammatory cytokine, has a crucial role in limiting the immune response to infection thereby preventing inflammation and excessive damage to the host (22) Several groups have previously identified prognostic values for IL-10 for prediction of bacteraemia, either on its own in FN in children (23)(24)(25)(26) or in combination with PCT in FN in adult patients (27). However, the vast majority of these data are generated from small, single centre studies that have investigated the various markers in isolation.…”
Section: Discussionmentioning
confidence: 99%